THE ONLINE SHOPPING HABITS AND E-LOYALTY OF GEN Z AS NATIVES IN THE DIGITAL ERA - Risca Fitri Ayuni (Journal of Indonesian Economy and Business (JIEB), 2019)
Introduction: Generation Z (Gen Z) refers to the most application-friendly and website-savvy generation engaging with the Internet for most of its daily activities. The number of Gen Z members has been growing and is projected to become the largest market segment by 2020. In the future, Gen Z will affect business strategies; compounded by the presence of a fourth industrial revolution (Industry 4.0), which will encourage companies to change their business models. One of the changes is a new paradigm shift by companies from the traditional business model to an internet-based business model (e-business model/e-commerce), such as online shops. Online shops have escalated at a rapid pace and have changed people’s buying habits, especially for Gen Z. Gen Z seems to be shopping online more than ever. Targeting them is the best strategy to enhance their lifetime loyalty. Background Problem: This study aims to examine the relationship of e-service quality, online customer value, e-satisfaction and e-loyalty. Research Method: Two hundred and forty-one Gen Z respondents were involved in this study. PLS 3, Sobel and SPSS 23 were employed to analyze the data. Five hypotheses were proposed. Findings: The findings indicated that e-service quality became the expected predictor of online customer value and satisfaction. In addition, the results confirm the mediating role of online customer value between e-service quality and e-satisfaction, as well as clarifying the relationship of online customer value and e-satisfaction. Finally, the effect of e-satisfaction on e-loyalty has been proven in this study. Conclusion: Upon figuring out the relevant issue, online shops are able to re-consider their business models to adopt the Industry 4.0 revolution, to strengthen their capacity in tight competition. In order to target Gen Z, who mostly do their purchasing via the Internet, online shops must provide high quality websites and create values which convey economic, social and functional values. These two key factors play significant roles in attaining Gen Z’s e-satisfaction, thus securing Gen Z’s e-loyalty.